The relationship between primary dysmenorrhea and physical activity in adolescent girls at SMP Negeri 2 Jatinangor in the working area of Cisempur Community Health Center - Nadia sriharyani; Akhmad Faozi; Iis Aisyah (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Adolescents often experience challenges related to reproductive health, especially regarding menstruation which occurs monthly. Menstruation is a natural phenomenon of bleeding from the uterus, indicating the maturity of the reproductive organs. Although common, a large number of young women in Indonesia face issues such as discomfort during menstruation, such as dysmenorrhea. Of course, menstrual pain can be caused by various factors, one of which is physical activity. The physical activities carried out by each young woman are of course different. This study aims to determine the relationship between primary dysmenorrhea and physical activity in adolescent girls at SMP Negeri 2 Jatinangor in the working area of Cisempur Community Health Center. This type of research uses quantitative analytics with a cross-sectional approach. The research sample used a total sampling technique, involving 205 female students as respondents. The tools used in this research included a questionnaire with a Numeric Rating Scale (NRS) and a questionnaire regarding physical activity of adolescent girls with an ordinal scale, which were then analyzed using a univariate approach. Data analysis was carried out by chi-square test, the majority of respondents, namely 96 respondents (46.8%) experienced mild primary dysmenorrhea. Most respondents experienced moderate physical activity, namely 124 respondents (60.1%). Based on the bivariate test, the p value = 0.051 (p <= 0.05). This shows that H0 is accepted so that there is no relationship between primary dysmenorrhea and physical activity at SMP Negeri 2 Jatinangor in 2024. The lighter the level of primary dysmenorrhea, the lighter the physical activity faced by young women at SMP Negeri 2 Jatinangor.